2016
DOI: 10.5219/599
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological and chemical quality of fresh and frozen whole trout and trout fillets

Abstract: The rainbow trout (Oncorhynchus mykiss) is considered as an important fish in the freshwater aquaculture and play a significant role in the human diet. The final quality of fish depends on the chemical and microbiological quality of fish at the time of freezing as well as on other factors including storage temperature and processing. The purpose of the study was to determine the microbiological status of 30 samples cooled and frozen trouts collected from approved farm in the Turiec region, territory of middle … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 21 publications
2
12
0
2
Order By: Relevance
“…In the FWF and FGF samples, it was detected that the TVB-N values increased throughout the storage period and were 13.38±1.39 and 12.87±0.81 on average at the end of the storage. The TVB-N values detected this study were found to be similar to the findings detected in the silver carp (Hypophthalmichthys molitrix) mince [59], while they were found to be higher than the values found in the whole trout and trout fillets (Oncorhynchus mykiss) samples [32].…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…In the FWF and FGF samples, it was detected that the TVB-N values increased throughout the storage period and were 13.38±1.39 and 12.87±0.81 on average at the end of the storage. The TVB-N values detected this study were found to be similar to the findings detected in the silver carp (Hypophthalmichthys molitrix) mince [59], while they were found to be higher than the values found in the whole trout and trout fillets (Oncorhynchus mykiss) samples [32].…”
Section: Discussionsupporting
confidence: 85%
“…The freezing process, to be applied for protecting the appearance and texture, smell and taste, and extending the storage period of fish that are hunted/harvested freshly and are not subjected to any technological process provides advantages to consumers [32]. In the food safety of seafood, it is known that aquatic environment and relevant processes during hunting/harvesting and various production phases have a very close relationship with the hygienic quality of products [12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the mentioned studies, the amount of the used materials in food preservations was determined to be higher than as compared with the materials obtained from nanotechnology applications. Psychrophilic bacteria that are the major group of microorganisms responsible for the spoilage of fresh fish at cold storage temperatures (Gram & Huss, ) could mostly reach a high level in the fish fillets within 7 days under cold storage conditions (Popelka, Jevinová, & Marcinčák, ). Already, as can be seen from the results, nisin and curcumin‐loaded nanofibers (0.0432 g nisin and 0.72 × 10 −4 g curcumin) as a coating material efficiently limited the rapid increase in psychrophilic bacteria growth, particularly, in this cold storage period.…”
Section: Resultsmentioning
confidence: 99%
“…In the mentioned studies, the amount of the used materials in food preservations was determined to be higher than as compared with the materials obtained from nanotechnology applications. Psychrophilic bacteria that are the major group of microorganisms responsible for the spoilage of fresh fish at cold storage temperatures (Gram & Huss, 1996) could mostly reach a high level in the fish fillets within 7 days under cold storage conditions (Popelka, Jevinová, & Marcin cák, 2016).…”
Section: Total Psychrophilic Bacteria Growthmentioning
confidence: 99%